Antimicrobial prescribing pattern in a tertiary care teaching hospital: a pilot study - Rajopadhye, Bhagyashri D.; Palkar, Sonali H.; Pandit, Vijaya A.; Dhande, Priti P.; Kumar, Mahadevan; Lalwani, Sanjay K. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The emergence of antimicrobial resistance is a worldwide challenge threatening to negate the gains made by discovery of antimicrobial agents (AMAs). Antimicrobial Stewardship Program (ASP) is an important strategy for ensuring appropriate use of AMAs and controlling emergence of antibiotic resistance. Implementation of ASP must start with assessment of the current state of antimicrobial use. This study was therefore conducted to assess the prevalent prescribing patterns in a tertiary care hospital and identify gaps which warrant corrective intervention. Methods: This prospective pilot study presents analysis of the first 30 Patients from the medicine ward prescribed at least one antimicrobial agent during the two months of study period. Relevant data was collected in AMA record form. Appropriateness of AMAs was analyzed regarding selection as well as administration protocol as per the hospital antibiotic policy. Results: Out of the 60 AMAs prescribed to these patients, most commonly prescribed were cephalosporins (63.3%), anti-amoebics (26.6%) and macrolides (23.3%). Common diseases involved were urinary tract infection, acute gastroenteritis, sepsis and lower respiratory tract infections. Use of AMAs was found to be appropriate for the indication in 42 %, dose in 97%, duration 60 %, route 93% and frequency 90 %. Conclusions: This gap between the appropriate and the actual practice use of AMAs indicates an urgent need of rigorous implementation of ASP in order to avoid emergence of resistance and to conserve the sensitivity to the available AMAs.